Human Trafficking: A Systematic Review and Future Research Agenda - Andre Edwin Johannes; Bevaola Kusumasari; Agus Heruanto Hadna; Nunuk Dwi Retnandari (Magister Ilmu Administrasi Publik, 2023)
This study aims to examine the topic of human trafficking (HT) to outline the definition and typology of HT, stages of HT, research themes, and future research directions in HT studies. This study used a systematic literature method to analyze 229 articles from the social sciences category from the Scopus database. This study found that the definition of HT is complex. Thus, to define HT, scholars need to be specific about the context, characteristics, and typology of trafficking. There are many internal and external factors in mobilizing the victim's choice of victim's immigration into this crime's vortex. Hence, policymakers need to know the critical issues of victim preference in the HT stage. Ultimately, there are three primary themes in the HT topic. They are: (1) developing models and strategies for dealing with more effective ways to combat HT around the world, (2) exploring and further comprehending the social and cultural factors underlying HT in different regions, and (3) capacity-building countries and implementation of more effective policies to protect and assist trafficking victims. Our integrative literature review may be the most recent study to provide detailed information about each research stream of HT literature in the social sciences discipline. The results of our review are limited to HT publications in the social sciences field, which stemmed from Scopus.